2010
DOI: 10.1002/ppul.21357
|View full text |Cite
|
Sign up to set email alerts
|

Benefit of gluten‐free diet in idiopathic pulmonary hemosiderosis in association with celiac disease

Abstract: Lane-Hamilton syndrome refers to the uncommon co-occurrence of idiopathic pulmonary hemosiderosis and celiac disease (CD). Three children aged between 7 and 14 years with IPH were detected to have co-existing non-diarrheal CD. Institution of gluten-free diet in each of the three children resulted in amelioration of the pulmonary symptoms along with improvement of anthropometric parameters and hemoglobin over a short-term follow-up period of 8-17 months. Inhaled/oral steroids and immunosuppressants could be wea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 11 publications
3
46
0
1
Order By: Relevance
“…Malabsorptive, immunological and infectious causes were proposed to explain the correlation between both diseases [12,13,14]. It has been demonstrated that the introduction of GFD may improve ejection fraction; some patients benefit exclusively from a diet therapy associated with the discontinuation of the immunosuppressive treatment [9]. Our case report confirms such an approach with the recovery of ejection fraction with values >50% through a 4-year term and the complete discontinuation of anti-arrhythmic drugs.…”
Section: Diagnosis: Iph Associated With Dilated Cardiomyopathy and Cesupporting
confidence: 71%
See 1 more Smart Citation
“…Malabsorptive, immunological and infectious causes were proposed to explain the correlation between both diseases [12,13,14]. It has been demonstrated that the introduction of GFD may improve ejection fraction; some patients benefit exclusively from a diet therapy associated with the discontinuation of the immunosuppressive treatment [9]. Our case report confirms such an approach with the recovery of ejection fraction with values >50% through a 4-year term and the complete discontinuation of anti-arrhythmic drugs.…”
Section: Diagnosis: Iph Associated With Dilated Cardiomyopathy and Cesupporting
confidence: 71%
“…Subsequent follow-up is suggested in order to guarantee the reintroduction of the immunosuppressive treatment in case symptoms relapse [9]. …”
Section: Diagnosis: Iph Associated With Dilated Cardiomyopathy and Cementioning
confidence: 99%
“…13,14 De confirmarse dicha asociación, la incorporación de una dieta libre de gluten contribuye a lograr la remisión de la sintomatología y a mejorar el pronóstico de ambas entidades. 15 n BIBLIOGRAFÍA…”
Section: Discussionunclassified
“…(6) To that end, serology for antiendomysium and antigliadin antibodies should be performed even in the absence of gastrointestinal symptoms. (7) It is important to confirm the presence of celiac disease, because treatment with a glutenfree diet is known to assist in the resolution of all symptoms and to result in radiological improvement in most individuals, (8) as seen in this clinical case. Long-term nutritional follow-up is also important; it has been reported that poor adherence to the diet can reactivate respiratory and gastrointestinal symptoms.…”
Section: Letter To the Editormentioning
confidence: 98%